PENGARUH PENGUNAAN METODE “RULE OF THUMB PRICING” UNTUK MEMAKSIMUMKAN LABA PETERNAK AYAM BROILER DI KECAMATAN TUMPANG KABUPATEN MALANG - Dullah, Mohammad - (Manajemen & Bisnis Jurnal, 2017)
The increase in the real business sector in the field of broiler farms in this poor district of the statistics is very good, but will be inversely if studied in depth about the output (profit) generated by the breeders. Return on investment (ROI) on this business is relatively small, dependence on feed from factories, dependence of seeds, investment of making the cage is not small, not to mention the Human Resources and Management of breeders is low so it needs to be studied in depth so that the farmers this is not a loss. Because of the many problems that must be solved by the breeders, this study limits and focuses on efforts to increase broiler farmers profit in Tumpang District, Malang Regency. This research is titled "Rule of Thumb Pricing Method" To Maximize Profit of Broiler Chicken Breeder in Tumpang District of Malang Regency The purpose of this research is "The use of rule of thumb pricing method to give optimal profit for broiler breeder in Tumpang District of Malang Regency "The benefits that can be derived from the results of this study in general can be used as a reference for young entrepreneurs who want to jump in the field of broiler chickens so that they can manage costs well in order to maximize profits broiler chicken products. This research uses quantitative descriptive method for understand the phenomenon of what is experienced by research subjects such as behavior, perception, motivation, action holistically This research was conducted in District Tumpang Malang Regency 2017. The results of this study indicate that 1) Use of markup pricing or method of rule of thumb pricing done bybroiler breeders in District Tumpang Malang Regency showed a significant increase in profits, this can be seen from the results of regression analysis with t count of 6.651 with the level of sig = 0.00. 2) The use of Markup Pricing method conducted by broiler breeders in Tumpang District of Malang Regency will usually be done in certain seasons, such as the New Year, Islamic Day and Natalan where the market is very much in need of broiler chicken supplying, so even though the price is fixed consumers buy these products because they need them